Determinants of E-Learning and Blended Learning Effectiveness: A Systematic Review of Student Outcomes and Engagement - Ansari, Mohammad Sultan Ahmad (Breakthroughs Information Technology, 2025)
Objective: This study aims to identify and synthesize key factors that influence the effectiveness of e-learning and blended learning, as well as their impact on learning outcomes, student satisfaction, and engagement through a systematic and comprehensive analysis of global literature from 2015 to 2025. Research Design & Methods: A Systematic Literature Review (SLR) guided by PRISMA procedures was conducted using Scopus, ScienceDirect, ERIC, and Web of Science. Boolean search strategies and eligibility screening yielded 150 relevant peer-reviewed articles. Bibliometric mapping using VOSviewer and thematic analysis were used to classify the findings into five determining clusters: technological, pedagogical, individual, social, and institutional.Findings: This review shows that the effectiveness of learning in a digital environment arises from the interaction between robust technological infrastructure, high-quality instructional design, learner readiness, social presence, and institutional support. Engagement and satisfaction serve as mediating variables that connect these determinants with learning outcomes. Trends indicate a shift in global research from emergency online learning to sustainable, quality-oriented digital education.Implications & Recommendations: Institutions need to strengthen infrastructure and training, educators need to increase interaction and collaboration, while future research should focus on AI personalization and learning analytics to strengthen evidence of the effectiveness of digital learning.Contribution & Value Added: This study presents an integrated conceptual model that synthesizes previous findings and provides a holistic understanding of the factors that shape the effectiveness of e-learning and blended learning, while strengthening the global literature and supporting evidence-based decision-making in digital education transformation.